Effects of Semaglutide on Symptoms, Function, and Quality of Life in Patients With Heart Failure With Preserved Ejection Fraction and Obesity: A Prespecified Analysis of the STEP-HFpEF Trial - Kosiborod, Mikhail N; Verma, Subodh; Borlaug, Barry A; Butler, Javed; Davies, Melanie J; Jon Jensen, Thomas; Rasmussen, Søren; Erlang Marstrand, Peter; Petrie, Mark C; Shah, Sanjiv J; Ito, Hiroshi; Schou, Morten; et al. (Circulation (New York, N.Y.), 2024)
BACKGROUND: Patients with heart failure (HF) with preserved ejection fraction (HFpEF) and obesity experience a high burden of symptoms and functional impairment, and a poor quality of life. In the STEP-HFpEF trial (Research Study to Investigate How Well Semaglutide Works in People Living With Heart Failure and Obesity), once-weekly semaglutide 2.4 mg improved symptoms, physical limitations, and exercise function, and reduced inflammation and body weight. This prespecified analysis investigated the effects of semaglutide on the primary and confirmatory secondary end points across the range of the Kansas City Cardiomyopathy Questionnaire (KCCQ) scores at baseline and on all key summary and individual KCCQ domains. METHODS: STEP-HFpEF randomly assigned 529 participants with symptomatic HF, an ejection fraction of ≥45%, and a body mass index of ≥30 kg/m2 to once-weekly semaglutide 2.4 mg or placebo for 52 weeks. Dual primary end points change in KCCQ-Clinical Summary Score (CSS) and body weight. Confirmatory secondary end points included change in 6-minute walk distance, a hierarchical composite end point (death, HF events, and change in KCCQ-CSS and 6-minute walk distance) and change in C-reactive protein. Patients were stratified by KCCQ-CSS tertiles at baseline. Semaglutide effects on the primary, confirmatory secondary, and select exploratory end points (N-terminal pro-brain natriuretic peptide) were examined across these subgroups. Semaglutide effects on additional KCCQ domains (Total Symptom Score [including symptom burden and frequency], Physical Limitations Score, Social Limitations Score, Quality of Life Score, and Overall Summary Score) were also evaluated. RESULTS: Baseline median KCCQ-CSS across tertiles was 37, 59, and 77 points, respectively. Semaglutide consistently improved primary end points across KCCQ tertiles 1 to 3 (estimated treatment differences [95% CI]: for KCCQ-CSS, 10.7 [5.4 to 16.1], 8.1 [2.7 to 13.4], and 4.6 [-0.6 to 9.9] points; for body weight, -11 [-13.2 to -8.8], -9.4 [-11.5 to -7.2], and -11.8 [-14.0 to -9.6], respectively; Pinteraction=0.28 and 0.29, respectively); the same was observed for confirmatory secondary and exploratory end points (Pinteraction>0.1 for all). Semaglutide-treated patients experienced improvements in all key KCCQ domains (estimated treatment differences, 6.7-9.6 points across domains; P≤0.001 for all). Greater proportion of semaglutide-treated versus placebo-treated patients experienced at least 5-, 10-, 15-, and 20-point improvements in all KCCQ domains (odds ratios, 1.6-2.9 across domains; P<0.05 for all). CONCLUSIONS: In patients with HFpEF and obesity, semaglutide produced large improvements in HF-related symptoms, physical limitations, exercise function, inflammation, body weight, and N-terminal pro-brain natriuretic peptide, regardless of baseline health status. The benefits of semaglutide extended to all key KCCQ domains. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT04788511.
Keywords: Heart Failure; Stroke Volume; Obesity; Inflammation; kvalita života; lidé; srdeční selhání; zánět; Natriuretic Peptide, Brain; natriuretický peptid typu B; obezita; glukagonu podobné peptidy; Glucagon-Like Peptides; Quality of Life; tepový objem; Humans